Gene vaccination with naked plasmid DNA: mechanism of CTL priming (The Rockefeller University Press, 1996)
The injection of naked plasmid DNA directly into the muscle cells of mice has been shown to induce potent humoral and cellular immune responses. The generation of a cytotoxic T lymphocyte (CTL) response after plasmid DNA injection may involve the presentation of the expressed antigen in the context of the injected myocytes' endogenous major histocompatibility (MHC)-encoded class I molecules or may use the MHC molecules of bone marrow-derived antigen presenting cells (APC) which are capable of providing co-stimulation as well. To resolve which cell type provides the specific restricting element for this method of vaccination we generated parent-->F1 bone marrow chimeras in which H- 2bxd recipient mice received bone marrow that expressed only H-2b or H- 2d MHC molecules. These mice were injected intramuscularly with naked plasmid DNA that encoded the nucleoprotein from the A/PR/8/34 influenza strain, which as a single antigen has epitopes for both H-2Db and H- 2Kd. The resulting CTL responses were restricted to the MHC haplotype of the bone marrow alone and not to the second haplotype expressed by the recipient's myocytes. The role of somatic tissues that express protein from injected plasmids may be to serve as a reservoir for that antigen which is then transferred to the APC. Consequently, our data show that the mechanism of priming in this novel method for vaccination uses the MHC from bone marrow-derived APC, which are efficient at providing all of the necessary signals for priming the T cell.